2018
DOI: 10.1177/2325967118775664
|View full text |Cite
|
Sign up to set email alerts
|

Derotational Osteotomy of the Distal Femur for the Treatment of Patellofemoral Instability Simultaneously Leads to the Correction of Frontal Alignment: A Laboratory Cadaveric Study

Abstract: Background:Derotational osteotomy of the distal femur allows the anatomic treatment of patellofemoral maltracking due to increased femoral antetorsion. However, such rotational osteotomy procedures have a high potential of intended/unintended changes of frontal alignment.Purpose/Hypothesis:The purpose of this study was to perform derotational osteotomy of the distal femur and to demonstrate the utility of a novel trigonometric approach to address 3-dimensional (3D) changes on 2-dimensional imaging (axial compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…Osteotomies can be placed about the intertrochanteric, subtrochanteric, diaphyseal, or distal metaphyseal regions and fixed with a plate, an intramedullary nail, external fixator, or a combination thereof [43,104,105]. The literature has described corrective osteotomy in patients with radiographic femoral anteversion >20 • to 25 • [106][107][108][109] The effect of transverse plane correction on other planes is an important consideration [110,111]. Using computer modeling from CT data of a femur, Nelitz et al demonstrated that proximal femoral osteotomies created varus alignment and distal osteotomies created valgus alignment [112].…”
Section: Transverse Plane Malalignmentmentioning
confidence: 99%
“…Osteotomies can be placed about the intertrochanteric, subtrochanteric, diaphyseal, or distal metaphyseal regions and fixed with a plate, an intramedullary nail, external fixator, or a combination thereof [43,104,105]. The literature has described corrective osteotomy in patients with radiographic femoral anteversion >20 • to 25 • [106][107][108][109] The effect of transverse plane correction on other planes is an important consideration [110,111]. Using computer modeling from CT data of a femur, Nelitz et al demonstrated that proximal femoral osteotomies created varus alignment and distal osteotomies created valgus alignment [112].…”
Section: Transverse Plane Malalignmentmentioning
confidence: 99%
“…As regards three-dimensional alignment change in a femoral osteotomy, a cadaveric study by Imhoff et al. showed coupled rotational and coronal plane (varus/valgus) alignment changes occurring in corrective femoral osteotomy 14 Several clinical studies have examined the postoperative change in rotational alignment after OWHTO; however, the reported results are somewhat discordant. An increased internal rotation of the distal bony fragment (decreased tibial torsion) was shown in some studies, 13 , 15 while no significant postoperative change was noted in another study.…”
Section: Discussionmentioning
confidence: 99%
“…Since the alignment is three-dimensional in nature, the postoperative changes induced by osteotomy should be assessed on a three-dimensional basis; however, the analyses conducted in the majority of the previous relevant studies were limited to alignment on coronal plane. 9 , 10 , 11 In regards to high tibial osteotomy and distal femoral osteotomy, there have been some studies investigating rotational changes induced by the osteotomy, 12 , 13 , 14 , 15 , 16 while no study has investigated the change in rotational alignment after DLO.…”
Section: Introductionmentioning
confidence: 99%
“…However, Imhoff et al demonstrated, in a cadaveric study, the importance of the orientation of the cut in the distal femur to avoid changes in the coronal orientation of the limb, when a distal femoral derotational osteotomy is performed [27]. More importantly, by a single cut in the distal femur, the coronal and the rotational problem of the patient can be addressed by choosing the patient-specific oblique cut [28]; these promising results must be validated in the operating room. In summary, the planning of the derotational osteotomy must consider the effects in the coronal and sagittal planes and the patient-specific segment of femur maltorsion.…”
Section: Discussionmentioning
confidence: 99%